2018
DOI: 10.31413/nativa.v6i0.6210
|View full text |Cite
|
Sign up to set email alerts
|

Crescimento Inicial De Espécies Arbóreas Nativas Em Solos Degradados E Com Presença De Plintita No Bioma Cerrado, Brasília – Df

Abstract: A intensificação do processo de antropização somado às características dos solos do Cerrado, em grande parte oligotróficos e intemperizados, dificulta a regeneração natural das espécies florestais, sendo necessária a intervenção humana para recompor a paisagem natural. O presente estudo teve como objetivoindicar espécies para iniciar o processo de recuperação de áreas degradadas do Cerrado com presença de plintita e processo de erosão estabelecido. Desta forma, analisamos as taxas de incremento em diâmetro e a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
4
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 22 publications
3
4
0
1
Order By: Relevance
“…A survival rate of native species in degraded areas of the Cerrado less than 60% is considered low (Oliveira et al, 2015;Lima et al, 2018). On the other hand, a survival above 80% in the same condition is an excellent result (Lima et al, 2018). Some studies on the recovery of Cerrado degraded areas reported values similar to those found in this study.…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…A survival rate of native species in degraded areas of the Cerrado less than 60% is considered low (Oliveira et al, 2015;Lima et al, 2018). On the other hand, a survival above 80% in the same condition is an excellent result (Lima et al, 2018). Some studies on the recovery of Cerrado degraded areas reported values similar to those found in this study.…”
Section: Discussionsupporting
confidence: 75%
“…The values obtained in the soil of the Center for Technology Transfer for Dairy Zebu Breeds (CTZL) experiment suggest that it has a medium acidity. Studies carried out by Lima et al (2018) confirm that the survival of seedlings planted in degraded areas is proportional to the disturbance of edaphic conditions, that is, soils with high acidity and low fertility hinder the survival of the seedlings.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Um dos principais fatores de degradação é o desmatamento, pois a retirada da cobertura vegetal interfere nos diferentes ciclos biogeoquímicos e no equilíbrio dinâmico dos ecossistemas (LIMA et al, 2018). Devido ao grau avançado de degradação dos biomas do semiárido nordestino, especialmente a caatinga, uma alternativa para a recuperação é utilizar espécies de plantas nativas, que já são adaptadas às características da região, como por exemplo a Erythrina velutina (SILVA et al, 2016).…”
Section: Introductionunclassified